IrFC - An Ixodes ricinus injury-responsive molecule related to Limulus Factor C - Urbanová, Veronika; Hartmann, David; Grunclová, Lenka; Šíma, Radek; Flemming, Tina; Hajdušek, Ondřej; Kopáček, Petr (Developmental and comparative immunology, 2014)
Limulus Clotting Factor C is a multi-domain serine protease that triggers horseshoe crab hemolymph clotting in the presence of trace amounts of bacterial lipopolysaccharides. Here we describe and functionally characterize an homologous molecule, designated as IrFC, from the hard tick Ixodes ricinus. Tick Factor C consists of an N-terminal cysteine-rich domain, four complement control protein (sushi) modules, an LCCL domain, a truncated C-lectin domain and a C-terminal trypsin-type domain. Developmental expression profiling by quantitative real-time PCR revealed that the irfc mRNA is expressed in all stages including eggs. In tissues dissected from adult I. ricinus females, the irfc mRNA is present mainly in tick hemocytes and accordingly, indirect immunofluorescence microscopy localized IrFC intracellularly, in tick hemocytes. Irfc mRNA levels were markedly increased upon injection of sterile saline, or different microbes, demonstrating that the irfc gene transcription occurs in response to injury. This indicates a possible role of IrFC in hemolymph clotting and/or wound healing, although these defense mechanisms have not been yet definitely demonstrated in ticks. RNAi silencing of irfc expression resulted in a significant reduction in phagocytic activity of tick hemocytes against the Gram-negative bacteria Chryseobacterium indologenes and Escherichia coli, but not against the yeast, Candida albicans. This result suggests that IrFC plays a role in the tick primordial complement system and as such possibly mediates transmission of tick-borne pathogens.
Keywords: exprese genu; Gene Expression; RNA, Messenger; přirozená imunita; RNA interference; Male; klíště; Up-Regulation; Candida albicans; fagocytóza; molekulární sekvence - údaje; upregulace; prekurzory enzymů; Escherichia coli; mužské pohlaví; proteiny členovců; Tick Ixodes ricinus; Immunity, Innate; komplement; Innate immunity; Enzyme Precursors; Complement System Proteins; Animals; ženské pohlaví; Serine Endopeptidases; zvířata; serinové endopeptidasy; Limulus Clotting Factor C; Ixodes; Phagocytosis; Micrococcus luteus; Molecular Sequence Data; Borrelia; Female; messenger RNA; Arthropod Proteins; Complement